If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = x(2x + -1)(x + 4) Multiply f * x fx = x(2x + -1)(x + 4) Reorder the terms: fx = x(-1 + 2x)(x + 4) Reorder the terms: fx = x(-1 + 2x)(4 + x) Multiply (-1 + 2x) * (4 + x) fx = x(-1(4 + x) + 2x * (4 + x)) fx = x((4 * -1 + x * -1) + 2x * (4 + x)) fx = x((-4 + -1x) + 2x * (4 + x)) fx = x(-4 + -1x + (4 * 2x + x * 2x)) fx = x(-4 + -1x + (8x + 2x2)) Combine like terms: -1x + 8x = 7x fx = x(-4 + 7x + 2x2) fx = (-4 * x + 7x * x + 2x2 * x) fx = (-4x + 7x2 + 2x3) Solving fx = -4x + 7x2 + 2x3 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -4 + 7x + 2x2 Simplifying f = -4 + 7x + 2x2
| 2sin(x)=2-3cos^2(x) | | 40-19=3(x-4) | | 8-72y=95-15y | | 7x^2+2x-15=0 | | Y(1-x)DX+x(1+y)dy=0 | | 2t+4u=40 | | 27-17=5(x-8) | | 20x-16=18x+6 | | -(13+g)=-9 | | 61+4y-28=15y-9-4y | | 80=91x | | 2.9y+1.7=3.5+23y | | -2(-3x-1)-3=-4 | | 9y-9=7y+1 | | x+18+4x=-48-4x-51 | | 4(7x+5)-48x=10x-10 | | 9p+8q=108 | | 6x-12=4(x+7) | | 2cos^2(x)-4cos(x)=0 | | (9x^2-7)*(9x^2+7)= | | 2/9-3 | | 8P+4Q=68 | | x^2+ln(-x+4)= | | 2(x+5)=8is | | 25s^2-81=0 | | 13=5-13+3c | | 2x+-5y+9=0 | | 13=5+4a | | 7428=p*6 | | 13-5=4a | | f(x)=-120+5x | | g+g+g=(1+g) |